Peak inflation: Ist die Teuerungswelle gebrochen? - Ferdinand Fichtner; Simon Junker; Claus Michelsen; Thore Schlaak (Wirtschaftsdienst, 2022)
– The slight slowdown of consumer price inflation in Germany in November does not yet constitute the beginning of lower inflation rates. Even though energy prices are dragging inflation, producer prices have drastically increased in the past year. Our estimates indicate that inflation rates will remain close to current levels until the end of 2023 and decrease only in 2024. Given the current fragile economic situation, restrictive monetary policy is not recommended. Rather, central banks should act attentively to prevent raising inflation expectations.
Keywords: E31; E37; E60; 330; Inflation; Inflationsrate; Geldpolitik; Deutschland